A Comparative Study of Cyclic Fatigue of 10 Different Types of Endodontic Instruments: an in Vitro Study - Jorge Rubio; José Ignacio Zarzosa; Antonio Pallarés (University of Zagreb. School of Dental Medicine, 2019)
Objective: This study was designed to test the null hypothesis that there were no significant differences between size 25 files F360, F6 SkyTaper, Hyflex EDM, iRace, Neoniti, One Shape Protaper Next, Reciproc, Revo-S and Wave One Gold in terms of resistance to cyclic fatigue and length of broken fragments. Material and methods: 300 new size 25 files of the systems studied were selected (n=30). The instruments were mechanized with a X-Smart Plus endo motor at the speed and torque recommended by the manufacturer, holding the instruments steady with a clamping mechanism, with passive adjustment and without pressure in a stainless-steel block. The time was calculated in seconds until fracture. The number of fatigue cycles was calculated as (Resistance (s) x Speed)/60. The separated fragment lengths were measured with a digital Vernier calliper. A statistical analysis was performed with the SPSS 18 programme at a 95% confidence level, using the Levene´s Test to compare variances, the Welch's Test to compare means, and the Games-Howell´s Test to reveal differences between groups. Results: The Levene's Test showed no equal variances (P<0.05). The Welch's Test (P<0.05) showed significant differences in cyclic fatigue and separated fragment lengths. The Games- Howell test (P<0.05) exhibited significant differences in multiple comparisons (P<0.05). Conclusions: The systems with CM-Wire (Hyflex EDM and Neoniti) were superior in resistance to the other systems for cyclic fatigue. For separated fragment lengths, F360 (conventional NiTi) and Reciproc (M-Wire) were better significantly better in terms of resistance.